Analisis Kinerja Keuangan Menggunakan Metode EVA Dan MVA Terhadap Return Saham Yang Dimoderasi Oleh Ukuran Perusahaan - Yiswi Oktavia Permatasari; Muji Gunarto (Global Leadership Organizational Research in Management, 2024)
The aim of this research is to analyze the effect of financial performance using the EVA and MVA methods on stock returns by including firm size as a moderating variable. The research uses a quantitative approach. The research population is food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2021-2022 period. Using a purposive sampling technique, a sample size of 27 companies was obtained with a population of 40 companies. Analyzed using the SEM-PLS approach to test the hypothesis. The results of the research found that company performance had a significant effect on stock returns using the EVA and MVA methods. However, firm size has no effect on stock returns, so the firm size variable cannot moderate financial performance using the EVA and MVA methods on stock returns. This proves that the company has not been able to create added value to the company and firm size cannot determine the continuity of a company's business.